Resins and gums in historical iatrosophia texts from Cyprus - a botanical and medico-pharmacological approach - Andreas eLardos; José ePrieto-Garcia; Michael eHeinrich; Michael eHeinrich (Frontiers Media S.A., 2011)
This study explores historical iatrosophia texts from Cyprus from a botanical and medico-pharmacological point of view focusing on remedies containing resins and gums. The iatrosophia are a genre of Greek medical literature of Byzantine origin and can be described as medicine handbooks which serve as therapeutic repositories containing recipes or advice. To extract and analyse information on plant usage in such sources - which are largely unedited texts and so far have not been translated - we investigate i) the relationship of the iatrosophia to Dioscorides' De Materia Medica as well as historic pharmaceutical books or standard texts on modern phytotherapy and ii) the validity of the remedies by comparing them to modern scientific data on reported biological activities. In the six texts investigated 27 substances incorporating plant exudates are mentioned. They are obtained from over 43 taxa of higher plants and in particular are used to treat dermatological, gastrointestinal and respiratory tract conditions. The comparison to historic pharmaceutical books and phytotherapy texts reflects the gradual decline of the use of plant exudates in Western medicine. While remarkable parallels to Dioscorides' text exist, the non-Dioscoridean influence suggests a complex pattern of knowledge exchange. Overall, this resulted in an integration of knowledge from so far poorly understood sources. The comparison with bioscientific data reveals a fragmentary picture and highlights the potential of these unexplored substances and their uses. Where relevant bioscientific data are available, we generally found a confirmation. This points to a largely rational use of the associated remedies. Taken together, the iatrosophia are a valuable resource for ethnopharmacological and natural product research. Most importantly they contribute to the understanding of the development of herbal medicines in the (Eastern) Mediterranean and Europe.